Plasma mannose level, a putative indicator of glycogenolysis, and glucose tolerance in Japanese individuals. Issue 4 (24th February 2017) - Yoshimura, Kumiko; Hirano, Seiki; Takata, Hiroshi; Funakoshi, Shogo; Ohmi, Satoko; Amano, Eri; Nishi, Yuichi; Inoue, Mari; Fukuda, Yoshiharu; Hayashi, Hikari; Taguchi, Tadao; Yamada, Shuhei; et al.
Abstract : We elucidated the relation between plasma mannose level and glucose tolerance in humans. These results are compatible with the results using rats in which mannose derived from glycogenolysis plays an important role in alteration of mannose levels after glucose loading. Abstract: Aims/Introduction: Mannose is a monosaccharide constituent of glycoproteins and glycolipids. Experiments in rats have shown previously that the plasma mannose level decreases after glucose load, but does not decrease in diabetic rats, and that hepatic glycogenolysis is a source of this plasma mannose; however, these results are not fully elucidated in humans. Plasma mannose levels before/after glucose loading in humans with various degrees of glucose intolerance were examined to analyze their association with clinical factors. Materials and Methods: The 75‐g oral glucose tolerance test was carried out in Japanese individuals not taking diabetes medications. Participants were classified into normal glucose tolerance, impaired glucose metabolism and diabetes mellitus groups. Insulinogenic index as an index of insulin secretion, and Matsuda Index as an index of insulin sensitivity were calculated. Mannose was assayed by the established method using high‐performance liquid chromatography after labeling. Results: After glucose load, the plasma mannose level decreased gradually in the normal glucose tolerance group, but did not decrease in the diabetes mellitus group. Plasma mannose changes during 120 min from baseline (M120 ‐M0 ) were significantly different among the three groups (normal glucose tolerance: −16.7 ± 1.7; impaired glucose metabolism: −9.0 ± 1.9; diabetes mellitus: −1.4 ± 1.8 μmol/L [ n = 25 in each group], P < 0.0001). Plasma glucose 120 min after glucose loading ( R 2 = 0.412) or loge ‐insulinogenic index, loge ‐Matsuda Index and age ( R 2 = 0.230) were determinants of M120 ‐M0 in multiple regression analyses. Conclusions: We clarified the relationship between plasma mannose level and glucose tolerance in humans. The present results are compatible with those using rats, in which mannose derived from glycogenolysis plays an important role in the alteration of mannose levels after glucose loading.